Modeling of potential flows with unknown boundaries on the basis of stationary discrete vortices - Averkova, O.A.; Logachev, I.N.; Logachev, K.I. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
A method to model the detached flows at the inlet of a suction port in multiply connected regions with cuts (fine visors) is proposed. The method allows one to construct free streamlines and velocity fields and to determine the local drag coefficient at the inlets of such channels. The reliability and adequacy of the method are demonstrated by comparison with numerical results obtained by the Zhukovskii method and with experimental data. A number of dependencies are found between the detached flow parameters at the inlet of a plane channel with two visors and their location and geometric sizes.